Multiple Atropo Selectivity by κ2‐N,O‐Oxazoline Urea Ligands in Cobaltaelectro‐Catalyzed C─H Activations: Decoding Selectivity with Data Science Integration - Philipp Boos; Neeraj Kumar Pandit; Suman Dana; Tristan von Münchow; Airu Hashidoko; Laura Haberstock; Regine Herbst‐Irmer; Dietmar Stalke; Lutz Ackermann (ChemistryEurope)
Enantioselective catalysis is one of the most prominent strategies in organic synthesis to access chiral bioactive compounds and advanced organic materials. Particularly, the development of chiral ligands has significantly advanced the efficiency and selectivity of transition metal‐catalyzed enantioselective transformations. Over recent decades, numerous chiral ligand classes with distinct geometrical and electronic properties have been established. Despite these advances, the demand for novel, tunable, and highly effective chiral ligands persists, driven by the need for structurally diverse chiral molecules and the pursuit of greener, more sustainable catalytic processes. Herein, a novel class of chiral oxazoline ureas is introduced and their potential as κ2‐N,O‐preligands in enantioselective transition metal catalysis is demonstrated. The chiral oxazoline urea ligands are featurized and compared with amide and enol derivatives using the physical organic descriptors. A multivariate linear regression model is constructed to quantitatively describe the effect of the quinoline fragment from the substrate and the ligand on enantioselectivity. Moreover, the model is effectively applied to atropo‐enantioselective cobaltaelectro‐catalyzed C─H annulations of 1‐alkynyl indoles.